SACRED ECHOES IN SECULAR MELODIES: PHILOSOPHICAL AND RELIGIOUS INTERPRETATIONS OF MODERN CHINESE VOCAL MUSIC - Song, Congju (European journal for philosophy of religion, 2024)
The mid-19th century marked a pivotal transition in Chinese society from a predominantly feudal structure to a more complex semi-colonial and semi-feudal society. This transformation was paralleled by the introduction of Western musical philosophies, including concepts of self-discipline and heteronomy, which began to permeate the Chinese cultural landscape. As these Western ideas took root, they significantly influenced the development of China's traditional vocal music, leading to a distinctive dichotomy between the musical traditions of the North and the South—epitomized by the emergence of four renowned singers and four notable Xusheng in the North, and the Nantong Linggong Society and Qipai styles in the South. This paper delves into the impact of foreign musical philosophies on Chinese vocal traditions, exploring the profound synthesis of spirit and material in music philosophy. It posits that vocal music represents a unique amalgamation of human anatomical structure and the spiritual world. By examining how these philosophical influences merged with the social milieu of the time, the study reveals how modern Chinese vocal music not only encapsulated the characteristics of the era and national identity but also echoed the populace's aspirations. These interactions underscored the music's role in reflecting spiritual and philosophical undercurrents, thereby laying a foundational stone for the resurgence of national vocal music in contemporary times, imbued with both secular and sacred resonances.